Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Dirty river: A queer femme of color dreaming her way home - Piepzna-Samarasinha, Leah Lakshmi (Arsenal Pulp Press, 2015)
Finaliste du Prix littéraire Lambda et du Prix Judy Grahn pour la non-fiction lesbienne En 1996, la poète Leah Lakshmi Piepzna-Samarasinha, portant seulement deux sacs à dos, a pris un bus Greyhound en Amérique et s'est enfuie au Canada. Iel s'est retrouvé.e à Toronto, où iel a été accueilli.e par une communauté de punks queer de couleur offrant des promesses d'amour et de révolution, mais iel est resté.e hanté.e par les raisons pour lesquelles iel a quitté la maison en premier lieu. Ce mémoire passionné et captivant est un mélange de rêves et de cauchemars, de files d'attente devant les tribunaux de l'immigration et de soirées dansantes queer sud-asiatiques ; Il s'agit d'une feuille de route intensément personnelle et d'un récit tragi-comique intersectionnel qui révèle comment une femme queer handicapée de couleur et survivante d'abus navigue sur la rivière sale d'un passé pas si lointain et, comme le suggère le sous-titre, « rêve de rentrer chez elle ». "
Keywords: amériques; approches et analyses; canada; capacitisme; identités LGBTQIA2+; mémoire collective; queer; queer of color; racisme; récit de vie; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; états-unis